Discovery and Characterization of Potent Thiazoles versus Methicillin- and Vancomycin-Resistant Staphylococcus aureus - Mohammad, Haroon (J Med Chem, 2014)
Methicillin- and vancomycin-resistant Staphylococcus aureus (MRSA & VRSA) infections are growing global health concerns. Structure-activity-relationships of phenylthiazoles as a new antimicrobial class have been addressed. We present 10 thiazole derivatives that exhibit strong activity against 18 clinical strains of MRSA and VRSA with acceptable PK profile. Three derivatives revealed an advantage over vancomycin by rapidly eliminating MRSA growth within six hours and no derivatives are toxic to HeLa cells at a concentration of 11 μg/mL.